Rancangan Model Bisnis Produk Berbahan Dasar Bioplastik Menggunakan Business Model Canvas dan Peta Empati (Fakultas Ekonomi, Universitas Ichsan Gorontalo, 2022)
Plastic waste management is a problem because plastic is a material that cannot be decomposed naturally (non-biodegradable). Bioplastics are used as a substitute for conventional plastics because they degrade quickly and are environmentally friendly. One way to overcome environmental problems regarding plastic waste is necessary to make changes to the raw materials of the plastic. This study aims to analyze consumer wants and needs regarding bioplastic products and develop a business model design for products made from bioplastics. This research method uses the design thinking method with the stages of analyzing the empathy map and the business model canvas (BMC). The results showed that the market segmentation was dominated by people aged 18-25 years. In addition, respondents want the type of product made from bioplastics that are produced as a food or beverage container with good quality and durability and an attractive design. The marketing strategy that can be done is to sell products online and promote products at significant events such as expos and bazaars.